2012
DOI: 10.3109/14767058.2012.663167
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and kidney in preterm infant

Abstract: In pre- and post-natal period nutrition can influence the function of many organs, including the kidneys. Intrauterine growth restriction and low weight at birth are associated with reduced nephron number, a risk factor for later cardiovascular and renal diseases. The development of such adult diseases may be favored, in animals, by additional risk factors, including postnatal overnutrition and/or rapid postnatal growth. In preterm infants, during the first weeks of life, high values of serum urea are presents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…The correlation between PMA and urinary metabolite profiles has been reported previously [17,31,32], and may reflect the degree of organ development and metabolic maturity. Between the first and the third week of life the glucogenic amino acids glycine, threonine, hydroxyproline and tyrosine increased along with metabolites of the tricarboxylic acid cycle like 2-oxoglutarate, citrate, fumarate and succinate.…”
Section: Discussionsupporting
confidence: 73%
“…The correlation between PMA and urinary metabolite profiles has been reported previously [17,31,32], and may reflect the degree of organ development and metabolic maturity. Between the first and the third week of life the glucogenic amino acids glycine, threonine, hydroxyproline and tyrosine increased along with metabolites of the tricarboxylic acid cycle like 2-oxoglutarate, citrate, fumarate and succinate.…”
Section: Discussionsupporting
confidence: 73%
“…The nephrons are the functional units of the kidney, hence, the number of nephrons formed within the kidney at completion of nephrogenesis directly influences lifetime renal functional capacity and reserve [29]; it is essential, therefore, that adequate nephrogenesis is achieved at the very beginning of life. Autopsy studies over the past two decades have demonstrated that there is a wide range in nephron number in the human kidney [3038]; overall, nephron number has been shown to range from approximately 200,000 to over 2 million per kidney [39].…”
Section: Iugr and Preterm Birth Adversely Impact On Nephrogenesismentioning
confidence: 99%
“…A normal range of Ca/P will lead to optimal bone mineralization and bone formation 17,22,44) . The Ca/P of native bone hydroxyapatite (HA) is 1.67 in human, so most bone related bioactive materials aims at this criteria.…”
Section: Discussionmentioning
confidence: 99%